Analisis Wacana Kritis Puisi “Munajat 212” Karya Neno Warisman Analisis Model Teun A. Van Dijk - Astri Wijayanti; Bambang Djunaidi; Suryadi Suryadi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
This research was aimed to describe the text structure, social cognition and social context in the poem “Munajat 212” by Neno Warisman. The theory used is Critical Discourse Analysis by Teun A. Van Dijk's model which has three dimensions. Analysis of text structure, social cognition, and social context. The method used is descriptive method. The research data were obtained through internet searches related to manuscripts and video documentation of the reading of the poem "Munajat 212". The data collection technique of this research is documentation technique, while the data is analyzed using the Teun A. Van Dijk model. The results of the validation of the analysis by two experts include linguistic experts and literature experts. The results of the analysis describe three elements of the Teun A. Van Dijk AWK model. Text structure analysis with three aspects in it. On the macro structure, theme of the poem is the manifestation of the author's prayer on social, political, religious and cultural phenomena in the dynamics of democratic life in Indonesia. Superstructure, the arrangement of stanzas that are interrelated. Micro structure, which contains a detailed element, meaning, lexicon, metaphor, sentence form, pronouns, graphics, expressions. Social cognition that discusses the author's personal situation regarding his assessment of social, political and cultural phenomena in the 2019 presidential choice, people's assessment of him, assessment of the role of authors, the media, the security apparatus and also the government, and how the authors understand the events around them. Finally, the social context, where the practice of power by the government tends to be arbitrary, and takes advantage of the easy access to power through the security apparatus to carry out its propaganda. Based on the research results, it can be concluded that the poem "Munajat 212" contains the meaning of text structure, social cognition and social context according to Teun A. Van Dijk's AWK model. Suggestions for this research are expected that the president and his staff can take a flexible attitude, and this research can open eyes to cases that befall Muslims in Indonesia and the world.